On thermal control of devices contained in inclined hemispherical cavities with dome oriented downwards and subjected to transient natural convection - Bairi, A.; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2014)
In this study, relationships of Nusselt-Rayleigh-Fourier type are proposed for the case of air-filled hemispherical cavity whose dome is oriented downwards and maintained isothermal. Its disk is subjected to a constant heat flux and inclined at an angle varying between 90 (vertical position) and 180 degrees (disk horizontal with dome oriented downwards). The numerical approach is performed in transient regime by means of the finite volume method for Rayleigh numbers in the range of 10(4) - 5 x 10(8). These results are confirmed at steady state by measurements done for some configurations in a previous study for the same Rayleigh and inclination ranges. Otherwise, they complete other surveys considering inclination angles varying between 0 degrees (horizontal cavity with dome oriented upwards) and 90 degrees (vertical cavity) for a wider range of Rayleigh numbers. The correlations allow thermal control of devices submitted to natural convection in hemispherical cavities during the time preceding the steady state after their switch on. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Thermal control; Nu-Ra-Fo correlations; Transient natural convection; Hemispherical cavity